Optimasi Proses Hidrolisis Biji Sorgum untuk Fermentasi Bioetanol dan Pemanfaatan Komponen Padatannya - Banon Rustiaty (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
Sorghum bicolor (Sorghum bicolor, L Moench) is very strong as a raw material for bioethanol industry. In various areas have emerged small bioethanol factories made from raw sorghum sapodilla. In order to optimally utilize sweet sorghum plant as raw material of bioethanol, besides the utilization of sorghum juice should also be attempted to use sweet sorghum seeds as raw material by efficient process method. In the hydrolysis of seeds still need assessment of pretreatment process because the process of starch hydrolysis inhibited by the matrix protein or protein body attached to the starch of sorghum starch. In order to improve the utilization of sorghum plant as raw material of bioethanol production, it is necessary to conduct a study to obtain efficient hydrolysis process conditions and optimum bioethanol conversion and able to produce other useful products. From the data obtained, it is known that sorghum seeds can be used as raw materials of bioethanol both local varieties and Numbu varieties. Differences in the results of DE (Dextrose equivalent) do show treatment with perendalaman in NaOH solution slightly better than with treatment without immersion, and it also affects the fermentation results that can produce greater ethanol. The optimum condition of sorghum seed process for local varieties (Hermada) and Numbu (sweet sorghum) was achieved under immersion conditions with 0.05 % NaOH at 45 °C for 1.5 hours. The fermentation ratio for Local varieties (Hermada) with immersion of NaOH is 86.75 %, without immersion 85.81 %. Meanwhile, the fermentation ratio for Numbu varieties with immersion of NaOH was 89.67 %, without immersion 87.68 %. For 2 (two) varieties of sorghum that were tried, did not show significant differences between treated and without treatment.